Risk screening, nutrition assessment and associated factors of malnutrition among elderly inpatients in Hue University of Medicine and Pharmacy Hospital - Che, Thi Len Len; Hoang, Thi Bach Yen; Nguyen, Minh Tam (Tạp chí Y Dược Huế, 2023)
Background: Undernutrition is a significant risk factor for mortality, complications, hospital infections, length of hospital stay, quality of life, and prognosis. Patients with proper nutrition will help prevent undernutrition, prevent the development of the disease, and improve the effectiveness of treatment. Nutrition is an integral part of the comprehensive treatment process. Nutritional risk screening is one criterion that shows the hospital’s nutritional care capacity. Assessing nutritional status plays an essential role in treating and recovering health. This study aims (1) to screen and assess the nutritional status of inpatients aged from 60 years old in Hue University Medicine and Pharmacy Hospital and (2) to identify some factors related to malnutrition. Methods: A cross-sectional study was carried out on 389 inpatients at two departments of internal medicine, Hue University of Medicine and Pharmacy Hospital, from 11/2020 - 03/2021. We used the mini nutritional assessment tool for screening nutrition risks. The subjective global assessment tool was used to assess nutritional status and questionnaires to understand some related factors. Results: There were 68.9% of patients at risk of malnutrition and 38.8% of patients had malnutrition. There were significant relationships between the nutrition status of patients with re-admitted status (p < 0.05), including diseases (p < 0.05), oral pathology (p < 0.05), decreased taste (p < 0.05). Conclusion: The prevalence of inpatients with nutritional risk in two departments of internal medicine was relatively high. It is necessary to conduct nutrition screening in all inpatients to improve the effectiveness of treatment and comprehensive care.